Eat pray love - Murphy, Ryan, 1965-; Roberts, Julia, 1967-; Crudup, Billy, 1968-; Franco, James, 1978-; Gilbert, Elizabeth, 1969- (Culver City, CA : Sony Pictures Home Entertainment, 2010)
After a painful divorce, a woman decides to travel to Italy, India, and Indonesia to discover the benefits of food, prayer, and true love.
Based on the book by Elizabeth Gilbert.
Originally released as a motion picture in 2010.
Features: includes both the theatrical version and director's cut of the film, movie making insights from director Ryan Murphy.
Julia Roberts, Billy Crudup, James Franco, Viola Davis, Richard Jenkins.
MPAA rating: PG-13.
DVD, Dolby digital 5.1 surround.
Keywords: Gilbert, Elizabeth, -- 1969- -- Film adaptations; Man-woman relationships -- Drama; Divorced women -- Drama; Italy -- Drama; India -- Drama; Indonesia -- Drama; Romance films; Video recordings for the hearing impaired; Video recordings for people with visual disabilities; Fiction films; Feature films